Template-induced polymorphic selectivity: the effects of surface chemistry and solute concentration on carbamazepine crystallisation - Parambil,JV; Poornachary,SK; Tan,RBH; Heng,JYY (Crystengcomm, 2014)
Cooling crystallisation of carbamazepine solution in glass vials functionalised with different silane molecules resulted in preferential nucleation of metastable form II or stable form III polymorphs within a definite range of supersaturation. In contrast, the two crystal forms nucleated concomitantly on a control substrate under similar solution conditions.